Large wetted areas of divertor power loads at Wendelstein 7-X. (3rd July 2020) - Niemann, H.; Drewelow, P.; Jakubowski, M. W.; Puig Sitjes, A.; Cannas, B.; Gao, Y.; Pisano, F.; König, R.; Burhenn, R.; Hacker, P.; Reimold, F.; Zhang, D.; et al.
Abstract: Wendelstein 7-X(W7-X), an optimized stellarator, conducted its first divertor operation. It uses an island divertor concept for the heat and particle exhaust. Large wetted areas of up to 1.5 m 2 have been reached, showing the benefits of the divertor concept and very efficient heat flux spreading. Moreover, a positive scaling of the wetted area with increasing SOL power is observed, which is important for operations at high input power. A definition of the wetted area is made based on thermographic camera observations for the 3D structure of W7-X with comparability to the definitions of other machines (e.g. tokamaks).